Early trajectories of skin thickening are associated with severity and mortality in systemic sclerosis - Ledoult, Emmanuel; Launay, David; Béhal, Hélène; Mouthon, Luc; Pugnet, Grégory; Lega, Jean-Christophe; Agard, Christian; Allanore, Yannick; Jego, Patrick; Fauchais, Anne-Laure; Harlé, Jean-Robert; Berthier, Sabine; et al. (Arthritis research & therapy, 2020)
Background Systemic sclerosis (SSc) is a severe and highly heterogeneous disease. The modified Rodnan skin score (mRSS) is a widely used tool for the assessment of the extent and degree of skin thickness. This study aimed to identify the classes of patients with early similar skin thickening trajectories without any a priori assumptions and study their associations with organ involvement and survival. Methods From the French SSc national cohort, patients with a disease duration of less than 2 years at inclusion and with at least 2 mRSS available within the first 4 years of follow-up were enrolled. Classes of patients with similar mRSS trajectories were identified based on a latent class mixed model. The clinical characteristics and survival rate were compared between the obtained classes. Results A total of 198 patients fulfilled the inclusion criteria, with a total of 641 mRSS available. The median disease duration and follow-up were 0.8 (interquartile range 0.4; 1.2) and 6.3 (3.8; 8.9) years, respectively. Individual trajectories of mRSS were highly heterogeneous between patients. Models with 1–6 latent classes of trajectories were sequentially assessed, and the 5-class model represented the best fit to data. Each class was characterized by a unique global trajectory of mRSS. The median disease duration did not differ significantly between classes. Baseline organ involvement was more frequent in classes with significant change over time (classes 2–5) than in class 1 (low baseline mRSS without significant change over time). Using Cox regression, we observed a progressively increasing risk of death from classes 1 to 5. Conclusions Early identification of clinical phenotype based on skin thickening trajectories could predict morbi-mortality in SSc. This study suggested that mRSS trajectories characterization might be pivotal for clinical practice and future trial designs.